(untitled) (Sains Humanika, 2011)
Islamic finance products has grown rapidly in the current banking and financial industry. This situation can be seen by the increasing of Islamic banking assets each year in addition to the participation of more institutions offering Islamic products. Islamic home financing products in Islamic banks use the concepts of Murabahah, Bay ‘Bithaman Ajil (BBA), BBA commodities, Ijarah Thumma Bay ‘, Istisna’ and Musharakah Mutanaqisah (MM). BBA concept is the most mode of financing use in Islamic home financing products, while others use the concept of MM. MM is a hybrid contract–based on partnerships. This concept was applied in banking practice in Malaysia since 2000. The concept of equity–based are very much encouraged to be used in the Islamic muamalat than debt–based concepts such as the BBA. Hence, this study will analyze the advantages of the products based on the concept of MM with a focus on home financing products offered by Kuwait Finance House Malaysia Berhad (KFHMB).